Dimensions of legal and moral use of artificial intelligence in education - Kronivets, Tetiana; Yakovenko , Olena; Tymoshenko , Yelyzaveta; Ilnytskyi, Mykhailo (Review of Artificial Intelligence in Education, 2024)
The purpose of the research is to critically analyze the legal aspects of the use of artificial intelligence (AI) in the field of education, as well as to study the role of chatbots and the Chat GPT model, plagiarism issues, educational modeling and the impact of AI on the labor market. To achieve this goal, various research methods are used, including the analysis of current legal norms and international legislation that relate to the use of AI in education. The study also includes an analysis of intellectual property issues, data privacy, ethical standards and liability. The results of the study highlight the problem of plagiarism in chat rooms and emphasize the importance of careful use of information to ensure academic integrity. Despite the possible misuse of AI by students, such as chatbots and GPT models, for plagiarism, these technologies can also facilitate plagiarism detection. The research also examines the use of machine learning and data analytics to create personalized learning experiences, improve learning effectiveness, and retain knowledge. The overall conclusion is that the integration of artificial intelligence in education has the potential to improve the quality and accessibility of education, but this requires a sound legal framework. The article also evaluates the effectiveness of various AI tools, including chatbots that provide information on demand and Chat GPT, useful for processing textual materials. The paper also examines the role of learning simulation in personalizing education, using AI to analyze performance data, and tailoring individual learning pathways.